Perhitungan Kapasitas CFM dan Biaya Kerugian untuk Mengetahui Keefektifan Kinerja pada AHU di Terminal Bandar Udara - Fatra, Oka; Novariski, Muhammad Samudera; Wijaya, Dewa Ayu Putu Laksmi Putri; Matalino, Mahatma; Arifin, Rayhan Abid; Del Piero, Muhammad Fadhillah (Jurnal Teknik Mekanikal Bandar Udara, 2023)
Since the official revocation of PPKM throughout Indonesia on 30 December 2022. The number of passengers, especially international passengers, at I Gusti Ngurah Rai International Airport has increased by 235% compared to the number of arrivals in 2021. Terminal temperature measurements are routinely carried out in the customs area at the international terminal in July and August proving that something was wrong with the performance of the distribution components of cold air to the area. However, due to reasons of convenience and lack of the number of workers, the inspections were not completely held optimal. So the research was done to find out the main cause of the calculation method is to look for the CFM value in the current AHU condition which will then be compared with the standard AHU CFM value. In addition, the amount of loss incurred in both conditions (current and standard conditions) is also calculated to find out which option produces lower costs and shows a higher level of effectiveness.